Prevention of complications in remote period after operational treatment of patients with nodular goiter on background autoimmune thyroiditis - M. I. Sheremet; V. O. Shidlovsky; L. P. Sidorchuk (Kazimierz Wielki University, 2017)
This article presents results of apoptosis detection among blood lymphocytes from the patients with autoimmune thyroiditis (AIT) at euthyroid and hypothyroid conditions. Contents of CD95+, annexin V-presenting (apoptotic) cells and TNF-α in blood were analyzed. It was shown, that altered regulation of programmed lymphocyte death in autoimmune thyroid disorders is demonstrated by increased content of TNF-α, INF-γ and CD95+ lymphocytes, being accompanied by decreased numbers of apoptotic cells in blood. After the complex treatment, positive dynamics of the disturbed parameters of the immune status was noted, first of all, the normalization of the disturbed balance of the subpopulation of apoptotic T-lymphocytes and antibodies to thyroglobulin and thyroid peroxidase, decrease in the content of cytokines, and returning to the limit of normal values of thyroid hormones levels. The application of the proposed therapeutic tactics and the diagnostic and treatment complex allowed to reduce the probability of progression of autoimmune and oxidative processes in the thyroid residue (by 79.3%), to exclude the probability of the development of relapses of the nodal goiter on the background of autoimmune thyroiditis.